Mine Water and the Environment - Mine Water and the Environment (Springer Nature, 2026)
Founded in 1981 (as the International Journal of Mine Water), Mine Water and the Environment presents original contributions addressing technical questions and practical issues related to the evaluation, prediction, prevention, or control of water problems at mining operations or their impact on the environment. Both the journal and its audience are interdisciplinary. Published papers convey new technical information by and for researchers and practitioners in this field. Coverage includes laboratory and field experiments, modeling efforts, studies of relevant field sites, technical evaluations of new technology, and engineering applications.
FI 0.56
Q3
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Recursos hídricos; Minería; Impacto ambiental